Ground dynamics and man-made processes prediction, design and management - Skipp, B. O. (Thomas Telford, 1998)
Based on the proceedings of the ICE Ground Dynamics conference held in November 1997, this volume addresses the onset of damage to the ground under dynamic loading and the prediction of deformations and structural loads under large soil strains.